A case study on the assessment of the level of technological unpackaging - Shah, Md. Alamgir; Sharif, M. N.; Pakorn Adulbhan; Techapun Raengkhum; Government of the United Kingdom (Bangkok : Asian Institute of Technology, 1977)
Import- substitution industries are concerned with different level of technological unpackaging. It is imperative on the part of developing countries to emphasize on increased level of unpackaging and identify the most suited level of unpackaging that can be possible within the limited supply of local inputs and available technology. The purpose of this study was to investigate the prospect of technological unpackaging at different levels and find the desired level of such unpackaging for an ongoing electric refrigerator manufacturing industry having its location in a developing country. Although there is no well-established analytical technique or methodology that is available for assessment of technological unpackaging, the study has included a comprehensive investment analysis and the other technical, economical and social considerations. Often many environmental factors are not easy to evaluate and for this, subjective judgement could play an important role to forecast the benefits and impacts that may arise due to changes in the level of unpackaging. The study has shown distinctly at three different levels of unpackaging and that, in this particular case, if the present level of unpackaging of 31 per cent could be increased to 78 per cent having more investment and subject to a few constraints, the project could add more technical and economic benefits, and in the process, it would meet many social needs and solve few concerns. Technological improvements due to increased level of unpackaging in one sector of economy, the advancement would follow in other related sectors to attain increased productivity. The other important fact is that an increase in the level of unpackaging, it would tend to decrease the amount of control exercised by the technology supplier countries over the technology recipient countries.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1977
Keywords: Technology assessment